A Chrismas Carol - Dicken, Charles (Lahore Readings Publishing, 2016)
Uses the classic story of "A Christmas carol" to develop listening comprehension, reading, pronunciation and critical thinking skills in English.
Include Illustration
Keywords: Dickens, Charles, 1812-1870